Archaeobotanical Studies in Poland – Historical Overview, Achievements, and Future Perspectives - Monika Badura; Maria Lityńska-Zając; Mirosław Makohonienko (Acta Societatis Botanicorum Poloniae, 2022)
Archaeobotany is the study of relationships between humans and the plant world in the past based on the analysis of plant remains preserved at archaeological sites. These studies provide us an opportunity to elucidate the history of farming economy based on transformations of plants and the natural environment caused by human activities. The present review aims to track the history of development of archaeobotanical studies in Poland, which have influenced our contemporary way of perceiving the past, as well as to present the selected and most important achievements in this field. Specifically, we emphasize the enormous contribution of Polish studies to broadening our understanding of the botanical past of Europe and the world. To the best of our knowledge, this work represents the first comprehensive attempt to summarize over a hundred-year-old activity of archaeobotanists in Poland.